2021
DOI: 10.1038/s41598-021-00529-7
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and cytotoxic capacity of pyroligneous extracts films of Eucalyptus grandis and chitosan for oral applications

Abstract: Chitosan films containing distilled pyroligneous extracts of Eucalyptus grandis (DPEC), characterized and developed by Brazilian Agricultural Research Corporation—Embrapa Temperate Agriculture (EMBRAPA-CPACT), were evaluated for antimicrobial activity against Candida albicans, Streptococcus mutans, and Lactobacillus acidophilus by direct contact test. Further, their capacity for the prevention of teeth enamel demineralization and cytotoxicity in vitro were also determined. The natural polymers were tested at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(61 reference statements)
0
3
0
1
Order By: Relevance
“…Several researchers stated that some medicinal plants extract may contain secondary metabolites like essential oils, flavonoids, alkaloids, triterpenoids, and phenolic compounds which can be effective against S. mutans, a microorganism involved in the development of dental caries. [2][3][4]10,11,15 The variations in chemical structure and molecular weight for each compound might be the cause of the different antibacterial effects. The amount of hydroxyl groups and the length of the hydrocarbon chain vary among aromatic hydrocarbons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers stated that some medicinal plants extract may contain secondary metabolites like essential oils, flavonoids, alkaloids, triterpenoids, and phenolic compounds which can be effective against S. mutans, a microorganism involved in the development of dental caries. [2][3][4]10,11,15 The variations in chemical structure and molecular weight for each compound might be the cause of the different antibacterial effects. The amount of hydroxyl groups and the length of the hydrocarbon chain vary among aromatic hydrocarbons.…”
Section: Discussionmentioning
confidence: 99%
“…2021 15 (In vitro study) Chitosan films containing distilled pyroligneous extracts of Eucalyptus grandis (DPEC) were evaluated for antimicrobial activity against Candida albicans, Streptococcus mutans, and Lactobacillus acidophilus by direct contact test.…”
Section: Souza Et Almentioning
confidence: 99%
“…Nevertheless, some research has revealed the safety of using this product in specific concentrations. An in vitro cytotoxicity test for developing a chitosan biofilm and WV for dental treatments demonstrated no cell cytotoxicity at 1500 and 7500 µg mL −1 [203]. In another in vitro study, toxicity of palm kernel WV to human skin cells was found [29].…”
Section: Wood Vinegar Toxicitymentioning
confidence: 98%
“…Neste sentido, o extrato pirolenhoso é uma alternativa na formulação de compostos antimicrobianos, fato já discutido por Souza et al (2021) que ressalta a capacidade de inibição desse à várias espécies bacterianas, incluindo até as reconhecidas por problemas da saúde bucal.…”
Section: Ensaio De Atividade Microbiológicaunclassified